Remittances, Trade Liberalisation, and Poverty in Pakistan: The Role of Excluded Variables in Poverty Change Analysis (The Pakistan Development Review, 2006)
This paper explores the impact of two shocks, trade liberalisation policies and decline in remittances, on welfare and poverty in Pakistan. It begins by reviewing the economy, which reveals that during the Nineties although import tariffs were reduced by 55 percent, poverty however remained higher in this period than in the Eighties. At the same time, Pakistan has experienced a slow down in the inflow of remittances, which reduces the incomes of households and puts pressure on the exchange rate resulting in reduction in the inflow of imports despite a reduction in import duties. Thus, in the absence of the effects of decline in remittances, the analysis of the impact of trade liberalisation policies may render biased results. This study overcomes this constriction and analyses the impact of trade liberalisation policies in the absence and presence of decline in remittances in a CGE framework with all the features necessary for trade policy analysis with poverty and remittances linkages. The simulation results show that a decline in remittances reduces the gains from trade liberalisation. The negative impact of remittance decline dominates the positive impact of trade liberalisation in urban areas. But, the positive impact of trade liberalisation dominates the negative impact of a decline in remittances in the case of rural areas. Poverty rises in Pakistan as a whole. It shows that the decline in remittance inflows is a major contributory factor in explaining the increase in poverty in Pakistan during the Nineties.